Numerical analysis of fluid flow due to mixed convection in a lid-driven cavity having a heated circular hollow cylinder - Billah, M.M.; Rahman, M.M.; Sharif, U.M.; Rahim, N.A.; Saidur, Rahman; Hasanuzzaman, M. (International Communications in Heat and Mass Transfer, 2011)
Mixed convection heat transfer in a lid-driven cavity along with a heated circular hollow cylinder positioned at the center of the cavity has been analyzed numerically. The present study simulates a realistic system such as air-cooled electronic equipment with a heat component or an oven with heater. A Galerkin weighted residual finite element method with a Newton-Raphson iterative algorithm is adopted to solve the governing equations. The computation is carried out for wide ranges of the Richardson numbers, cylinder diameter and solid fluid thermal conductivity ratio. Results are presented in the form of streamlines, isothermal lines, average Nusselt number at the heated surface and fluid temperature in the cavity for the mentioned parameters. It is found that the flow field and temperature distribution strongly depend on the cylinder diameter and also the solid-fluid thermal conductivity ratio at the three convective regimes.